Silencing of LINC00707 suppresses cell proliferation, migration, and invasion of osteosarcoma cells by modulating miR-338-3p/AHSA1 axis - Zhang Xiao-rong; Shao Jian-li; Li Heng; Wang Liang (Open Life Sciences, 2021)
Osteosarcoma is the most common type of primary malignant tumor of the bone, with a high metastatic rate and poor prognosis. Therefore, it is important to further elucidate the molecular mechanisms involved in the development of osteosarcoma and explore new molecular therapeutic targets. Long intergenic nonprotein-coding RNA 707 (LINC00707) is an oncogenic gene in several cancers. In this study, we further clarified its role and regulatory mechanism in osteosarcoma. We found that LINC00707 levels are significantly higher in the osteosarcoma cell lines SW 1353, HOS, U-2 OS, MG-63, and Saos-2 compared to those in human fetal osteoblastic cell line hFOB1.19. LINC00707 silencing suppressed cell proliferation, migration, and invasion of MG-63 and Saos-2 cells. Moreover, LINC00707 can act as a competitive endogenous RNA of miR-338-3p, and miR-338-3p inhibitor and AHSA1 overexpression alleviated the effect of LINC00707 silencing. In conclusion, we demonstrated high expression of LINC00707 in osteosarcoma cell lines and that silencing LINC00707 suppresses cell proliferation, migration, and invasion by targeting the miR-338-3p/AHSA1 axis in MG-63 and Saos-2 cells. These findings suggest that LINC00707 may serve as a potential target for osteosarcoma treatment.